Sistem Informasi Geografis Prioritas Penanganan Kerusakan Infrastruktur Menggunakan Metode MOORA - Silalahi, Adi Gunawan; Triase (LPPM Universitas Mulia, 2025)
The prioritization of road infrastructure damage repairs in Sibolga City has so far been conducted manually, resulting in inefficient, time-consuming processes that are prone to subjectivity. This study aims to develop a Geographic Information System (GIS) based on the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method to provide an objective and measurable solution for determining road repair priorities. Data were collected through field observations and interviews, and the system was developed using the Waterfall model. The MOORA method was applied to evaluate road segments based on several key criteria such as damage level, traffic volume, repair cost, and road width. The analysis results show that the system successfully ranks road segments accurately, with segments A21, A22, and A23 receiving the highest priority scores of 0.1096. The GIS feature enables visualization of priority locations on an interactive map, supporting coordination among stakeholders and enhancing public participation in monitoring and reporting processes.